LEGISLATIVE FOUNDATIONS OF ACCOUNTING THE RESULTS IN ENTERPRISE - Galushchak , I.Ye. (The actual problems of regional economy development, 2016)
In the article the economic content regulation and accounting results of the company, as well as theoretical and methodological bases of formation, assessment and recognition of accounting information on revenues and financial performance. These problems of accounting theory and practice of financial results are mentioned. The basic directions of improvement of accounting of financial results are outlined. Financial results of entities are profit or loss. Business activities in the field of financial results is aimed at ensuring a profit and its optimal allocation and use, and if the losses - to establish the causes and sources of coverage. Achieving a positive, balanced with the needs of financial results provided by focused management process of formation of profit based on comprehensive consideration of all external and internal factors affecting the production and sale of goods and services. JEL:M41